Corrosive Injuries Admitted to Hospitals of Rasht city during 2002-2009 - Morteza Rahbar Taromsari; Alireza Badsar; Keyvan Aminian; Habib Allah Abiar; Morteza Fallah karkan; Sina Montazeri; keyvan Abbasi (Iranian Journal of Toxicology, 2016)
Background: Caustics produce one of the most serious complications of poisonings. This research was aimed to study demographical, clinical and endoscopic findings in patients with corrosive injury. Methods: In a retrospective survey, all records of the patients who had been admitted to Razi and 17th Shahrivar hospital in Rasht city due to the ingestion of caustic agents during 2002-2009 and endoscopy had been performed for them in the first 24 hours after ingestion were studied. The information was analyzed by descriptive method using SPSS 16 software. Results: Among 258 patients in Razi Hospital, 174 (67.4%) were female with mean age of 29.33 years old. 127 patients (61.1%) had intentional ingestion. 208 patients were finally studied. Among them, 175 patients were hospitalized for 2 days (average 1.73 days). Among 45 patients of 17th Shahrivar hospital, 24 (53.3%) were female. All of them had accidental ingestion. The most frequent site of injury in adults was esophagus (37.2%) and in pediatric population was the mouth (66.6%). Of all pediatric patients, one case had grade IIb endoscopic injury. Among cases who underwent endoscopy (in adults),20.8%, 16.7%, 41.6%, 16.7%,4.2% had grade zero, I, IIa, IIb and III injury, respectively .In all cases, bleaches were the most frequent consumed material. Conclusion: In both studied groups, female patients were more affected by corrosive agents and in adults, intentional ingestion was approximately 1.5 times more frequent than the accidental cases; while all of pediatric patients had accidental poisoning. Most of the lesions had been received only medical treatment without any surgical interventions.